Imaging the Glycosylation State of Cell Surface Glycoproteins by Two‐Photon Fluorescence Lifetime Imaging Microscopy1. Issue 52 (20th November 2013) - Belardi, Brian; de la Zerda, Adam; Spiciarich, David R.; Maund, Sophia L.; Peehl, Donna M.; Bertozzi, Carolyn R.
<x xml:space="preserve">Abstract</x> Glycoproteins in focus: Metabolic labeling of glycans with azido sugars (see picture) in combination with two‐photon fluorescence lifetime imaging microscopy enables the visualization of specific glycoforms of endogenous proteins. This method can be utilized to detect glycosylated proteins in both cell culture and intact human tissue slices.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>